The Utilization of the Potential of Tahura K.G.P.A.A. Mangkunagoro I through the Development of MARBLE (Moss Android Mobile Learning) Application For 10thGrade Students on Bryophyte Learning - Fattahu Husna Nurisma; Muzzazinah Muzzazinah; Alanindra Saputra; Nurmiyati Nurmiyati (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2020)
The development of technology in the 21st century demands to use of technology in learning. However, it should apply contextual learning based on the surrounding environment. The misappropriation of technology and the lack of green areas in the school environment caused biology learning on bryophyte to be hampered. The use of technology in learning can create a fun atmosphere by combining the local potential and technology advancement. This innovation can be realized through developing learning media called MARBLE application. This study aims to: 1) utilize the potential of Tahura Mangkunagoro I for bryophyte learning, 2) produce the new learning media that is MARBLE application, 3) examine the advisability of MARBLE application. The type of research is Research and Development (R&D). This research applies the ADDIE model developed by Branch (2009) which consists of 5 stages, namely: analysis, design, development, implementation, and evaluation. The stages are carried out until the development stage because this study aims to determine the perceptions of teachers and students about the MARBLE application. The research was conducted from January to July 2020. The research was conducted in Tahura as a bryophyte sampling location.  MARBLE feasibility testing was conducted by three media experts, three material experts, one learning expert, and three biology teachers. Data collection was conducted by using a questionnaire. The technique of data analysis was descriptive quantitative obtained from the results of the questionnaire. The results showed that the MARBLE application was declared valid by material experts with a percentage of about 81.7%, media experts with a percentage of about 90%, and biology teachers with a percentage of about 90.3%. The average of all percentages is 87.42% with the most validcategory